The effect of specialized training using a specially designed device on learning the abdominal front kick skill among junior karate players - Hadi, Dr. Hamed Abdel Shaheed; Takhikh, Dr. Saleh Balash; Akab, Asst.L. Rami Salman; Sarhan, Prof. Dr. Salman Akab (Sulaimani Journal for Humanities, 2026)
The research problem became clear through monitoring and observing many educational and training methods, especially the motor path and accuracy of the two-leg skills. The researchers found a lack of use of educational methods that help in developing this skill in a good manner. Among the important skills in the sport of karate is the skill of the front kick to the abdomen. The objectives of the research are to prepare specialized exercises using a device designed to teach the skill of the front kick to the abdomen to junior karate players and to identify the differences between the cardio and posttests in the performance of the front kick skill by the junior karate players for members of the experimental group. As for the research hypothesis, there are no differences between the cardio and posttests in the performance of the skill of front kick to the abdomen among junior karate players for members of the experimental group. The researchers used the semi-experimental approach using one experimental group with two pre-tests and a descriptive post-test for its suitability and the nature of the research problem. The current research population consists of Al-Tadamon Junior Club players for the season (2024-2025) with karate effectiveness. The research samples were chosen according to the required procedures and the sample. The researchers randomly selected the sample of the exploratory experiment, which numbered (5) players, and the main experiment sample numbered (14). The most important conclusions are that the specialized exercises using the designed device contributed to learning the skill of the front kick to the abdomen among the junior players of the Solidarity Club in karate, while the most important finding was the adoption of the specialized exercises using the designed device in learning the skill of the front kick to the stomach among the junior karate players.
Keywords: Movement path; front kick; karate